Prevalence of disease related prion protein in anonymous tonsil specimens in Britain: cross sectional opportunistic survey. (21st May 2009) - Clewley, Jonathan P; Kelly, Carole M; Andrews, Nick; Vogliqi, Kelly; Mallinson, Gary; Kaisar, Maria; Hilton, David A; Ironside, James W; Edwards, Philip; McCardle, Linda M; Ritchie, Diane L; Dabaghian, Reza; et al.
Abstract : Objective To establish with improved accuracy the prevalence of disease related prion protein (PrP CJD ) in the population of Britain and thereby guide a proportionate public health response to limit the threat of healthcare associated transmission of variant Creutzfeldt-Jakob disease (vCJD). Design Cross sectional opportunistic survey. Study samples Anonymised tonsil pairs removed at elective tonsillectomy throughout England and Scotland. Setting National anonymous tissue archive for England and Scotland. Main outcome measure Presence of PrP CJD determined by using two enzyme immunoassays based on different analytical principles, with further investigation by immunohistochemistry or immunoblotting of any samples reactive in either assay. Results Testing of 63 007 samples was completed by the end of September 2008. Of these, 12 753 were from the birth cohort in which most vCJD cases have arisen (1961-85) and 19 908 were from the 1986-95 cohort that would have been also exposed to bovine spongiform encephalopathy through infected meat or meat products. None of the samples tested was unequivocally reactive in both enzyme immunoassays. Only two samples were reactive in one or other enzyme immunoassay and equivocal in the other, and nine samples were equivocally reactive in both enzyme immunoassays. Two hundred and seventy six samples were initially reactive in one or other enzyme immunoassay; the repeat reactivity rate was 15% or less, depending on the enzyme immunoassay and cut-off definition. None of the samples (including all the 276 initially reactive in enzyme immunoassay) that were investigated by immunohistochemistry or immunoblotting was positive for the presence of PrP CJD . Conclusions The observed prevalence of PrP CJD in tonsils from the 1961-95 combined birth cohort was 0/32 661 with a 95% confidence interval of 0 to 113 per million. In the 1961-85 cohort, the prevalence of zero with a 95% confidence interval of 0 to 289 per million was lower than, but still consistent with, a previous survey of appendix tissue that showed a prevalence of 292 per million with a 95% confidence interval of 60 to 853 per million. Continuing to archive and test tonsil specimens, especially in older birth cohorts, and other complementary large scale anonymous tissue surveys, particularly of post-mortem tissues, will further refine the calculated prevalence of PrP CJD .